Digital Literacy Competency of Primary School Teacher Education Department Student as the Demands of 21st Century Learning - Isrokatun, I.; Pradita, Avi Andini; Ummah, Sylvia Alfaeni; Amalia, Dita Yessi; Salsabila, Novia Shafa (Universitas Pendidikan Indonesia, 2022)
The 21st century is the era that involves the use of digital devices. Thus, pre-service teachers demand to have many competencies, which in this case is digital literacy competency. There are four digital literacy competencies: digital skills, digital culture, digital ethics, and digital safety. This study employs a qualitative method of research design with a study case. The data were collected by conducting interviews. The analysis in this study was carried out by making a detailed description of the digital literacy competencies of primary school teacher education students and adding a detailed view of the aspects in the research. The participants in this study were 30 primary school teacher education students at a university in Sumedang Regency. The results reveal that mastering digital skills will help daily life work; mastering digital culture will help preserve culture and protect creation; mastering digital ethics will avoid many conflicts; and mastering digital safety can be aware of many crimes in the digital world. Students as prospective teachers are expected to know, and understand and master digital literacy for future teaching.